2019
DOI: 10.1292/jvms.18-0674
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S degrades arresten and canstatin in infarcted area after myocardial infarction in rats

Abstract: The basement membrane surrounding cardiomyocytes is mainly composed of α1 and α2 chain of type IV collagen. Arresten and canstatin are fragments of non-collagenous C-terminal domain of α1 and α2 chain, respectively. We previously reported that the expression of canstatin was decreased in infarcted area 2 weeks after myocardial infarction in rats. In the present study, we investigated the regulatory mechanism for expression of arresten and canstatin. Myocardial infarction model rats were produced by ligating le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Furthermore, matrikine production can be increased upon tissue damage following an insult or injury. Exemplarily, type IV collagen matrikines arresten and canstatin are increasingly released by cathepsin S at the site of injury after myocardial infarction [110].…”
Section: Inflammation In Bm Degradation In Phmentioning
confidence: 99%
“…Furthermore, matrikine production can be increased upon tissue damage following an insult or injury. Exemplarily, type IV collagen matrikines arresten and canstatin are increasingly released by cathepsin S at the site of injury after myocardial infarction [110].…”
Section: Inflammation In Bm Degradation In Phmentioning
confidence: 99%
“…Cleavage product of collagen IVα1 by MT1-MMP and MT2-MMP [166]. Expression is decreased 1-day post-MI in rats but increased in an I/R pig model [174,175].…”
Section: Arrestenmentioning
confidence: 99%
“…in myofibroblasts derived from the infarcted area of MI model rats 12 . We also clarified that canstatin was highly expressed in normal myocardium, but decreased in the infarcted area of MI model rats 12,13 . Moreover, we recently reported that a long-term administration of recombinant mouse canstatin suppressed isoproterenol-induced cardiac hypertrophy and fibrosis 14 .…”
mentioning
confidence: 70%